Educação, Partido Fardado e neofascismo: a expansão das escolas cívico-militares na guerra cultural - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The expansion of civic-military schools in 2019 returned to the spotlight with the enactment of Decree No. 10,004, dated September 5, 2019, which established the National Program of Civic- Military Schools (PECIM). Through a bibliographical analysis, we identified a certain consensus that, in the context of the rise of neoconservatism, this initiative aimed to increase control over students, shape their identities, and suppress the critical and free education guaranteed in Brazilian public schools by the Federal Constitution of 1988 and the Law of Guidelines and Bases. According to Virgínia Fontes, the militarized educational model under the Bolsonaro federal administration (2019–2022) sought to establish low-cost police control in public schools, which is why the historian referred to them as "policed schools," a term we employ in the title and throughout this work. In this dissertation, beyond the effects on schools, we took a step back: we sought to understand who seeks to militarize school education and why, particularly in the context of the rise of post-2016 coup neofascism. To address this question, we examined the essence of Brazilian militarization and its motivations, drawing on the works of sociologist Florestan Fernandes. We also sought to investigate how the Armed Forces operate in favor of the dominant classes (bourgeoisie and landowners) and align with the extreme-right status quo, guided by an authoritarian ideology that has intensified throughout history. After the dictatorship period (1964–1988), the military became a kind of "fourth power," supported by constitutional mechanisms such as Article 142. The military police are part of the Army as auxiliary and reserve forces, governed by Article 144, which has remained virtually untouched since the dictatorship. Our hypothesis is that, unlike the "hybrid" format that already existed in Brazil (such as in Goiás), policed schools arise from a societal project developed and sustained by the Brazilian Armed Forces and neofascist civilian sectors. For the theoretical and methodological framework, we employed historical-dialectical materialism. Moreover, as a general objective, we aimed to diagnose the influence of the “Partido Fardado” (Armed Party) on the direction of Brazilian public school education. To achieve this, we defined specific objectives: 1) to understand the formation and militarization of the autocratic-bourgeois state; 2) to analyze the politicization of the Brazilian Armed Forces and their partisan role in the bourgeois autocracy; and 3) to investigate the originality of the expansion of civic-military schools in the context of the rise of neofascism. Our research object, studied through a documentary analysis, was the "2035 Nation Project," developed in 2022 by the Sagres Institute in partnership with the General Villas Bôas Institute and the Federalist Institute. By diagnosing the neoconservative and authoritarian elements in this document, it becomes clear that the formation of the populace is deemed essential to "undermine radicalisms" and disseminate what they call "evolutionary conservatism." Thus, we agree with the assessment that a cultural war is underway and that, under the neofascist government, the Ministry of Education became a sort of bunker (Leher; Santos, 2021). More than a conjunctural phenomenon or the particular interest of civilian governments, in our view, the militarization of school education was a tactic aimed at repositioning the systems of oppression/repression of the dominant classes, as well as bringing neoconservative, neofascist, and authoritarian conceptions closer to the core of public education and mass formation.
Keywords: Escolas cívico-militares; Militarização da educação; Neofascismo; Partido Fardado e educação; Escolas Policializadas; Civic-military schools; Militarization of education; Neofascism; Partido Fardado and education; Police-oriented schools; CNPQ::CIENCIAS HUMANAS::EDUCAÇÃO